Assessment Of The Knowledge, Attitudes And Practices On Qat Chewing Among Medical, Pharmacy And Dentistry Undergraduate Students In Aden University, Yemen - Al-Kaff, Mohammed Saleh Ahmed (2012)
Qat plant or Catha edulis Forsk is a species belonging to the plant family Celastraceae. The fresh leaves and buds of the qat plant contains cathinone, an amphetamine like stimulants responsible for most of its pharmacological action. One of the pharmacological actions is the ability to concentrate, and this has been used as an excuse for the students to use qat. This habit also can be found among the university students especially medical, pharmacy and dentistry. However, as other stimulants, this cathinone also has the ability to cause dependence to the users. This study is aimed to evaluate the knowledge, attitudes and practices on qat use among health care related undergraduate students in Aden University, Yemen. A cross-sectional study was carried out involving Medicine, Pharmacy and Dentistry students in Aden University. A validated questionnaire was distributed to all students using simple random sampling method. A total of 646 out of 672 students completed the questionnaire. The data were analyzed using Statistical Package for Social Science (SPSS) version 15.0. Chi-square was used to test the association of the student’s perception about the qat plant with socio-demographic factors.